Migration Patterns and the Changing Demographics of Nigeria - Adebayo, Esther (Journal of Physical Sciences, 2023)
Purpose: The main objective of this study was to investigate migration patterns and the changing demographics of Nigeria. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings revealed that there exists a contextual and methodological gap relating to the migration patterns and the changing demographics in Nigeria. Preliminary empirical review revealed the intricate relationship between migration dynamics and demographic transformations in Nigeria. It reveals that migration, both domestic and international, plays a pivotal role in shaping Nigeria's evolving population structure, particularly in terms of rapid population growth, a significant youth population, and urbanization. The research emphasizes the importance of understanding the demographic consequences of migration patterns and the economic drivers behind international migration. Ultimately, the study's findings hold significance for policymakers, urban planners, educators, and healthcare providers as they grapple with the challenges and opportunities presented by Nigeria's changing demographics, guiding evidence-based decision-making and sustainable development efforts. Unique Contribution to Theory, Practice and Policy: The Demographic Transition theory, Push and Pull theory and the Dependency theory may be used to anchor future studies on changing demographics. The recommendations from the study highlighted the importance of evidence-based policymaking, data collection, and community engagement. Policymakers should prioritize comprehensive urbanization and migration policies that consider resource allocation and services for a diverse, youthful population. It is crucial to establish a robust database and employ modern technology for monitoring migration trends. Additionally, fostering social cohesion and inclusivity through community-based programs and cultural integration initiatives is essential for peaceful coexistence in evolving urban areas.